EMOTIONAL AND EVALUATIVE LANGUAGE IN ENGLISH AND UZBEK POPULAR SCIENCE DISCOURSE - Yokubjonova, Shahnozabegim; Yokubjonova, Nodirabegim (International Conference on Business & Management, 2025)
The success of popular science writing depends heavily on the strategic use of emotional and evaluative language to foster intellectual curiosity and generate reader interest. This comparative study analyzes the linguistic devices used to express attitude and subjective assessment in English and Uzbek popular science texts. English often utilizes intensifiers (e.g., truly amazing, fundamentally different) and engagement markers to personalize discovery, operating within a model of constrained scientific enthusiasm. The analysis contrasts the prevalence of subjective vocabulary, the use of modality, and the function of writer involvement, highlighting how linguistic and cultural norms shape the emotional rhetoric available to the science popularizer. Understanding these differences is crucial for effective cross-cultural science communication